ARTIFICIAL INTELLIGENCE AND THE RIGHT TO LIFE: A PERSPECTIVE FROM SELECTED AFRICAN COUNTRIES - John Mubangizi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This article explores the intricate relationship between artificial intelligence (AI) and the fundamental human right to life, with a specific focus on the context of a few African countries. The article begins by establishing a contextual understanding of both AI and the right to life, examining their theoretical underpinnings and historical development. It then looks at the relationship between AI and the right to life and how AI technologies are being deployed in the selected African countries, particularly in contexts relevant to the right to life, such as healthcare, criminal justice, transportation and disaster response. The article then looks at the ethical considerations that arise from the intersection of AI and the right to life in African contexts particularly in the context of three contentious issues that the right raises, namely, the death penalty, abortion and euthanasia. This is followed by an overview of the legal and policy frameworks governing AI in these countries, and how they address concerns related to the right to life. The article concludes with lessons from the experiences of South Africa, Mauritius, Egypt, and Kenya in navigating the ethical challenges of AI governance, and recommendations on what these countries can learn from each other on one hand and what they can learn together, on the other.